Neurotype-Matching, but Not Being Autistic, Influences Self and Observer Ratings of Interpersonal Rapport - Crompton, Catherine J.; Sharp, Martha; Axbey, Harriet; Fletcher-Watson, Sue; Flynn, Emma G.; Ropar, Danielle (Frontiers in Psychology, 2020)
The Double Empathy Theory suggests that communicative difficulties between autistic and non-autistic people are due to bi-directional differences in communicative style and a reciprocal lack of understanding. If true, there should be increased similarity in interaction style, resulting in higher rapport during interactions between pairs of the same neurotype. Here, we provide two empirical tests of rapport, with data revealing whether self- and observer- rated rapport varies depending on the match or mismatch in autism status within a pair. An additional opportunity afforded by these data is to examine the effect of the autism status of the rater on the perceived rapport between matched and mismatched pairs. In Study 1 72 participants were allocated to one of three dyad conditions: autistic pairs (n = 24), non-autistic pairs (n=24) and mixed pairs (n=12 autistic; n=12 non-autistic). Each participant completed three semi-structured interactions with their partner, rating rapport after each interaction. Non-autistic pairs experienced higher self-rated rapport than mixed and autistic pairs, and autistic pairs experienced higher rapport than mixed pairs. In Study 2 (n = 80) autistic and non-autistic observers rated interactional rapport while watching videoed interactions between autistic pairs, non-autistic pairs, and mixed pairs (n=18, a subset of participants in Study 1). Mixed pairs were rated significantly lower on rapport than autistic and non-autistic pairs, and autistic pairs were rated more highly for rapport than non-autistic pairs. Both autistic and non-autistic observers show similar patterns in how they rate the rapport of autistic, non-autistic, and mixed pairs. In summary, autistic people experience high interactional rapport when interacting with other autistic people, and this is also detected by external observers. Rather than autistic people experiencing low rapport in all contexts, their rapport ratings are influenced by a mismatch of diagnosis. These findings suggest that autistic people possess a distinct mode of social interaction style, rather than demonstrating social skills deficits. These data are considered in terms of their implications for psychological theories of autism, as well as practical impact on educational and clinical practice.